Effect of Different pH Values on the Compressive Strength of Calcium-Enriched Mixture Cement - Sobhnamayan, Fereshte; Sahebi, Safoora; Alborzi, Ali; Ghorbani, Saeed; Sadat Shojaee, Nooshin (Iranian Endodontic Journal, 2014)
Introduction: The aim of this study was to evaluate the compressive strength of calcium-enriched mixture (CEM) cement in contact with acidic, neutral and alkaline pH values. Methods and Materials: The cement was mixed according to the manufacturer’s instructions, it was then condensed into fourteen split molds with five 4×6 mm holes. The specimens were randomly divided into 7 groups (n=10) and were then exposed to environments with pH values of 4.4, 5.4, 6.4, 7.4, 8.4, 9.4 and 10.4 in an incubator at 37° C for 4 days. After removing the samples from the molds, cement pellets were compressed in a universal testing machine. The exact forces required for breaking of the samples were recorded. The data were analyzed with the Kruskal-Wallis and Dunn tests for individual and pairwise comparisons, respectively. The level of significance was set at 0.05. Results: The greatest (48.59±10.36) and the lowest (9.67±3.16) mean compressive strength values were observed after exposure to pH value of 9.4 and 7.4, respectively. Alkaline environment significantly increased the compressive strength of CEM cement compared to the control group. There was no significant difference between the pH values of 9.4 and 10.4 but significant differences were found between pH values of 9.4, 8.4 and 7.4. The acidic environment showed better results than the neutral environment, although the difference was not significant for the pH value of 6.4. Alkaline pH also showed significantly better results than acidic and neutral pH. Conclusion: The compressive strength of CEM cement improved in the presence of acidic and alkaline environments but alkaline environment showed the best results.